Ocean Acidification's Effects on the Growth Rate and Haematological Markers of Asian Seabass (Lates calcarifer) - S., Karthikeyan; P., Sureshkumar; C., Dinakaran; A., Chezhian; Kolanjinathan, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Anthropogenic carbon dioxide (CO2) absorption in the seas is changing the chemistry of saltwater globally, which has an impact on marine biota. The increasing partial pressure of CO2 (pCO2) is shoaling the calcium carbonate saturation horizon in a number of regions, particularly high latitudes and those that connect with notable hypoxic zones. Early calcareous skeleton formation in marine organisms, especially fish, is directly impacted by the CO2 chemistry of seawater. Furthermore, CO2 alters the physiology of marine animals by reducing their ability to transfer oxygen and creating an acid-base imbalance. There is not enough study done at relevant pCO2 levels to help us predict future effects on food-web dynamics and other ecological processes. The seabass fingerlings are exposed to various pH levels over a duration of nine weeks. Ocean acidification (OA) levels were measured at pH 7.8, pH 7.5, and pH 8.1, which served as the control. Results revealed that fingerling of seabass had a greater impact on growth rate and haematological markers. The results also revealed that long term effect of OA leads to changes the red blood cells (RBCs) and white blood cells (WBCs) count, which indirectly affect the other haematological indices. We conclude that there is a tremendous deal of potential for broad alterations to marine ecosystems as a result of OA and the combined effects of other human stressors.